1983
DOI: 10.1139/v83-342
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid complexes of 1,2-diketones and their derivatives. The synthesis of seven-membered rings

Abstract: The structures and charge distributions of Lewis and complexes of butane-2,3-dione, 1, cyclohexane-1,2-dione, 2, and 2-methoxycyclohex-2-en-1-one, 5, have been investigated by 1H nmr spectroscopy. A 1:1 complex was formed between 1 and SnCl4 which appeared to have a bridged structure. In the case of 2 and 5 both oxygens were again involved in complex formation with TiCl4 or SnCl4. In each case the large downfield shift of the vinyl proton resonance, H3, indicated extensive charge delocalization within the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…[5] Most similar to our system is the Lewis acid-catalyzed [4 + 3] cycloaddition of 2-siloxyacroleins with dienes, which has been proposed to involve a stepwise process, in which the zwitterionic intermediate goes directly to the [4 + 3] cycloadduct. [21][22][23] Even though it has been shown that the Diels-Alder cycloadduct derived from cyclopentadiene and a 2-siloxyacrolein rearranges cleanly to the formal [4 + 3] cycloadduct, [18] computational studies suggest that this process occurs by a retro DielsAlder reaction followed by a [4 + 3] cycloaddition. [24] Therefore, we decided to conduct further studies to understand how the [4 + 3] cycloadducts in the reaction of 2-alkylacroleins and cyclopentadiene are formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Most similar to our system is the Lewis acid-catalyzed [4 + 3] cycloaddition of 2-siloxyacroleins with dienes, which has been proposed to involve a stepwise process, in which the zwitterionic intermediate goes directly to the [4 + 3] cycloadduct. [21][22][23] Even though it has been shown that the Diels-Alder cycloadduct derived from cyclopentadiene and a 2-siloxyacrolein rearranges cleanly to the formal [4 + 3] cycloadduct, [18] computational studies suggest that this process occurs by a retro DielsAlder reaction followed by a [4 + 3] cycloaddition. [24] Therefore, we decided to conduct further studies to understand how the [4 + 3] cycloadducts in the reaction of 2-alkylacroleins and cyclopentadiene are formed.…”
Section: Resultsmentioning
confidence: 99%
“…Such a ring closure of 19 would be much more reasonable when R is siloxy, especially if it is also accompanied by a silyl migration. [21][22][23] …”
Section: Resultsmentioning
confidence: 99%
“…9 1 H NMR spectra confirm that butane-2,3-dione is the major tautomeric form. 10 1,3-Butadiene-2,3-diols fit the definition of enediols. 11 Such compounds are more stable if there are bulky aromatic groups present in the molecule 11 or if there is a carbonyl group conjugated with the enolic CdCOH moiety.…”
Section: Introductionmentioning
confidence: 94%
“…13 On the other hand, titration of the ethanolic solution with bromine shows that diketone is probably contaminated with both mono-and dienol, PhCHdC(OH)C(OH)dCHPh. 10 Further, this highly conjugated compound was obtained in a pure form by recrystallization from benzene. 14 Formation of the strong hydrogen bond is also expected to be responsible for stabilization of 1,6-diketohexa-3,4dienediols (a in Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…Based on work by Childs 47 and Sasaki, 48 we reported the (4+3)-cycloaddition reaction of a silyloxyacrolein. Thus, treatment of 106 with 10 mol% of Sc(OTf) 3 in the presence of furan afforded the cycloadduct 107 in very high yield and complete diastereoselectivity (eqn ( 16)).…”
Section: ð13þmentioning
confidence: 99%